Getah virus triggers ROS-mediated autophagy in mouse Leydig cells - Li, Fengqin; Deng, Lishuang; Xu, Tong; Xu, Lei; Xu, Zhiwen; Lai, Siyuan; Ai, Yanru; Wang, Yanqun; Yan, Guangwen; Zhu, Ling (Frontiers in Microbiology, 2025)
IntroductionGetah virus (GETV) is a zoonotic virus transmitted via a mosquito-vertebrate cycle. While previous studies have explored the epidemiology and pathogenicity of GETV in various species, its molecular mechanisms remain largely unexplored.MethodsThis study investigated the impact of GETV infection and associated molecular mechanisms on reactive oxygen species (ROS) and autophagy levels in mouse Leydig cells both in vivo and in vitro. The male mice and TM3 cells were treatment with N-acetylcysteine (NAC) to reduce cellular ROS levels. Rapamycin (Rapa) and 3-Methyladenine (3- MA) were used to change autophagy in both infected and uninfected TM3 cells.Results and DiscussionThe findings revealed that GETV infection in mouse testes speciffcally targeted Leydig cells and induced oxidative stress while enhancing autophagy in testicular tissue. Using TM3 cells as an in vitro model, the study confirmed GETV replication in this cell line, triggering increased ROS and autophagy levels. Treatment with N-acetylcysteine (NAC) to reduce cellular ROS levels markedly reduced autophagy in testicular tissue and TM3 cells infected with GETV. Interestingly, the use of rapamycin (Rapa) and 3-Methyladenine (3- MA) led to autophagy change in both infected and uninfected TM3 cells, with no signiffcant alterations in cellular ROS levels. These results indicate that GETV infection elevates ROS levels, subsequently inducing autophagy in mouse Leydig cells. We also found that autophagy plays an important role in GETV replication. When autophagy levels were reduced using NAC and 3-MA, a corresponding decrease in TCID50 was observed. Conversely, upregulation of autophagy using Rapa resulted in an increase in TCID50 of GETV. Therefore, we speculate that GETV may exploit the autophagy pathway to facilitate its replication. These ffndings illuminate the interplay between GETV and host cells, providing valuable insights for therapeutic strategies targeting autophagy in GETV infections.